Current And Future Trends in the Teaching of Removable Partial Dentures in Dental Schools in Malaysia: A Cross Sectional Study - Umer Daood; Preena Sidhu; Nafij Bin Jamayet; Shivani Kohli; Normaliza Ab Malik; Seow Liang Lin; Igor R. Blum; Christopher D. Lynch; Nairn H.F. Wilson (Elsevier, 2024)
Indexed by WOS/SCOPUS/ERA